Gross characterization of ovarian follicular population in relation to developmental stage of corpus luteum in goat - SANGHA, G K; KHERA, K S; KAPIL, KANAN (The Indian Journal of Animal Reproduction, 2023)
Studies were carried out to observe the effect of age and stage of cycle on ovarian follicular dynamics ingoat ovary. 264 genitalia from non-descript goats were collected from the local slaughterhouse throughout theyear and classified into immature, mature, old and pregnant on the basis of color, condition and tonicity ofmuscles of uteri, oviducts and ovaries. Cyclicity of mature and old animals was further adjudged on the basis ofpresence and stage of corpus luteum. Maximum numbers of genitalia were observed from the mature class andminimum were that from pregnant. The total number offollic_les observed was more in immature ovary as comparedto mature and aged animals. Ovaries in late luteal phase of mature animals had more number of follicles perovary as compared to early luteal and follicular phase. In aged animals, the number of follicles/ovary did notdiffer significantly during different stages of estrous cycle. Rate ofatresia increased in mature and old animals ascompared to immature animals. Generally left ovary had more number of follicles as compared to the right.
Keywords: Atretic; Follicle; Goat; Non-atretic; Corpus luteum